Fructooligosaccharides in honey and effects of honey on growth of Bifidobacterium longum BB 536 - Soon, Jan Mei; Mohd Som, Mohd Nordin; Abdullah Sani, Norrakiah (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2010)
This research was carried out to determine the fructooligosaccharides content in local honey samples, namely the wild Malaysian Tualang honey and common wild honey obtained from Tapah, Perak and a commercial Tualang honey. Local wild honeys were found to contain a higher concentration of fructooligosaccharides (FOS) compared to the commercial Tualang honey. The FOS quantified from local wild honeys was inulobiose, kestose and nystose. Nystoses were found at a very low amount in the commercial Tualang honey. The effects of honey on the growth of Bifidobacterium longum BB 536 were investigated. Both wild and commercial honey samples including FOS standard were found to support the growth of B. longum. The pH value of the skim milk + honey inoculated with the probiotic strain decreases as expected. Addition of honey was found to support the growth of B. longum BB 536.